Production of Sustainable Concrete from Agro-Wastes ash - Hamdullah, Dhifaf (Iraqi Journal of Civil Engineering, 2023)
There are various means of recycling agricultural wastes to maximize economic benefit from it. According to environmental statistics, agricultural wastes is one of the most dangerous types of wastes, especially in villages, because it is disposed of by burning. In this study, production of natural ash from agro wastes was carried out. Two types of agro waste ash were produced through burning and grinding process. waste date tree and waste reeds ash. The waste date ash (WDA) and waste reeds ash (WRA) were included in concrete by replacement of a specific portion of cement weight (5%, and 10%). Moreover, a blend of the two types of ashes were also considered. Furthermore, the natural ash was utilized in production of green concrete. Hardened density and compressive strengths at various ages (7, 28 and 56 days) were evaluated. The results in this research showed an excellent increase in compressive strength at ages (7,28 and 56) days. When measuring the compressive strength at the late age (56 days), DPA + WRA it was the best model used if it recorded the highest increase in it. Also, the use of WRA10% gave a good result, increasing its strength of the reference mixture and the rest of the mixtures also gave good and remarkable results in increasing the resistance, as the use of ash in these mixtures protects the environment from pollution and gives mixtures of higher resistance and can be used as a partial substitute for cement, except for DPA10%, so the usual mixture was better than it.